Hemotoxicity of Hairy Fig (Ficus hispida L.f.) Fruits on Male Wistar Rats (Rattus norvegicus Berkenhout, 1769) - Fitria, Laksmindra; Sari, Annisa Lintang; Handayani, Lisa; Widiyanto, Slamet (Jurnal Biodjati, 2022)
Hairy fig (Ficus hispida) fruits (HFF) are widely consumed as food and traditional medicine in several West Asian countries, both the unripe fruit (UHFF) and ripe fruit (RHFF). However, they are not commonly utilized in Indonesia. Acute oral toxicity studies reported No Observed adverse effect level (NOAEL). Further, a reproductive toxicity study found that UHFF boosted spermatogenesis and increased the quality and quantity of spermatozoa. Meanwhile, RHFF exhibited the opposite effects. To provide comprehensive information from the previous study, this research was conducted to evaluate the hemotoxicity of UHFF and RHFF about their impact on the male reproductive system. Nine Wistar rats were assigned into three groups: the first group received UHFF juice, the second group received RHFF juice, and the third group received distilled water as control. The volume of each treatment was 2 mL/individual/day for 77 days. On days 0, 28, and 77, blood samples were collected for routine hematological profile examination using a hematology analyzer (SysmexÂ®XP-100). Data were analyzed using a one-way ANOVA test and Duncan's test (Î±=0.05) to discover significant differences between groups and times. Results showed that consuming hairy fig fruit, especially the UHFF, had an unfavorable effect on erythrocytes resulting in hypochromic microcytic anemia. Still, there was no adverse effect on leukocytes and platelets. Anemia may have occurred due to the presence of hemotoxic compounds that interfere with the synthesis and binding of hemoglobin or because the hairy fig fruit filtrates were oxidized, thereby increasing the level of oxidative stress within the body, of which is a drop in hemoglobin levels.